2022
DOI: 10.1017/s1460396922000127
|View full text |Cite
|
Sign up to set email alerts
|

Rural disparities in head and neck cancer from 2017 to 2021: a single institution analysis

Abstract: Introduction: This study aims to look at the trends in our head and neck cancer patient population over the past 5 years with an emphasis on the past 2 years to evaluate how the coronavirus disease 2019 (COVID-19) pandemic has impacted our disparities and availability of care for patients, especially those living in rural areas. An additional aim is to identify existing disparities at our institution in the treatment of head and neck patients and determine solutions to improve patient care. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Overall, acceptance of this type of care delivery was noted in adults and children, 16,21,22,29 but not all patients found telehealth a valuable mechanism for care. 21 A number of studies assessed the satisfaction of the patient and caregiver's use of telehealth platforms for care delivery. Broglio and Kirkland, 20 Cheung et al, 14 and Hutchinson et al 27 reported high levels of agreement that telehealth allowed patients to communicate easily with providers, meeting their needs and serving as equivalent to face-to-face office encounters.…”
Section: Characteristics Of Rural Telehealth Programsmentioning
confidence: 98%
See 4 more Smart Citations
“…Overall, acceptance of this type of care delivery was noted in adults and children, 16,21,22,29 but not all patients found telehealth a valuable mechanism for care. 21 A number of studies assessed the satisfaction of the patient and caregiver's use of telehealth platforms for care delivery. Broglio and Kirkland, 20 Cheung et al, 14 and Hutchinson et al 27 reported high levels of agreement that telehealth allowed patients to communicate easily with providers, meeting their needs and serving as equivalent to face-to-face office encounters.…”
Section: Characteristics Of Rural Telehealth Programsmentioning
confidence: 98%
“…[9][10][11][12] Of the articles reviewed, various study methods were used, such as randomized trials, [13][14][15][16][17][18] survey types, 19,20 and chart or data review. [21][22][23][24] The gray literature offered guidelines and policies for implementing and promoting effective virtual visits, as well as advocating for continuing coverage and payment of the various telehealth platforms 9-12 (Table 2).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations